Game-Based Learning in Improving The Pedagogic Competence of Prospective Elementary School Teachers: A Systematic Literature Review - Asri Widia Ningrum; Berta Apriza; Rohmani; Yasinta Mahendra; Bunga Adelia (Universitas Pendidikan Ganesha, 2025)
Strengthening the pedagogical competence of prospective elementary school teachers in the digital era is essential due to the growing demand for innovative, technology-integrated learning. Although Game-Based Learning (GBL) has strong potential to support this process, its implementation still faces conceptual and practical challenges. This study aims to critically analyze and synthesize scientific findings on the effectiveness of GBL in improving the pedagogical competence of prospective elementary school teachers. This study employs a Systematic Literature Review (SLR) approach guided by the PRISMA framework, analyzing ten relevant scientific articles published between 2020 and 2024. Data were collected through systematic searches of reputable academic databases and analyzed using thematic analysis techniques. The findings indicate that GBL contributes positively to the improvement of learning motivation, collaboration, creativity, digital competence, and the development of pedagogical mindsets that are adaptive to technology. Furthermore, direct involvement of prospective teachers in designing and playing educational games was found to have a more significant pedagogical impact than purely theoretical approaches. Nevertheless, implementation challenges remain, particularly concerning game design quality, educators’ readiness to act as facilitators, and variations in participants’ levels of experience. This study concludes that GBL represents a transformative approach in teacher education, with implications for the development of more practical, collaborative, and sustainably technology-integrated curricula.